Urethral leiomyoma: Common tumor at unusual site (Indian Journal of Case Reports, 2018)
Urethral leiomyoma is a rare benign mesenchymal neoplasm arising from the urethral smooth muscle. They produce diagnostic dilemma to the clinicians as it is a rare site for these tumors and these tumors should be differentiated from other urethral tumors. Here, we report the case of a 35-year-old female patient presenting with a mass attached to the anterior wall of the urethra. Histopathologic examination confirmed the diagnosis of leiomyoma.